2021
DOI: 10.1002/etc.5108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Acute Effects and Oxidative Stress Responses of Phenicol Antibiotics and Suspended Particles in Daphnia magna

Abstract: Suspended particles (SP) exist widely in various water systems and are able to adsorb other pollutants in water, producing ecotoxic effects on aquatic nontarget species. Until now, however, few studies have focused on the effects of SP on antibiotics. Therefore, the present study investigated the effects of the mixtures of SP and phenicol antibiotics (chloramphenicol [CAP], thiamphenicol [TAP]) on acute toxicity and oxidative stress responses in Daphnia magna. The results indicated that the acute toxicity of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Luo et al reported that lomefloxacin causes oxidative stress and induces cellular damage in Daphnia . The formation of ROS is a widely accepted mechanism by which antibiotic damage harms membrane lipids, proteins, and nucleic acids, eventually leading to changes in the physicochemical properties of the zooplankton, as well as damage or death. As the final breakdown product of lipid peroxidation, MDA has been widely used as an indicator of cellular oxidative damage in organisms under antibiotic stress . Zhang et al observed a substantial increase in the level of MDA when D. magna was exposed to chloramphenicol and thiamphenicol.…”
Section: Toxic Effects Of Antibiotics On Zooplankton Speciesmentioning
confidence: 99%
“…Luo et al reported that lomefloxacin causes oxidative stress and induces cellular damage in Daphnia . The formation of ROS is a widely accepted mechanism by which antibiotic damage harms membrane lipids, proteins, and nucleic acids, eventually leading to changes in the physicochemical properties of the zooplankton, as well as damage or death. As the final breakdown product of lipid peroxidation, MDA has been widely used as an indicator of cellular oxidative damage in organisms under antibiotic stress . Zhang et al observed a substantial increase in the level of MDA when D. magna was exposed to chloramphenicol and thiamphenicol.…”
Section: Toxic Effects Of Antibiotics On Zooplankton Speciesmentioning
confidence: 99%